Can Getting Enough Vitamin D during Pregnancy Reduce the Risk of Getting Asthma in Childhood? - Bountouvi, Evangelia; Douros, Konstantinos; Papadopoulou, Anna (Frontiers in Pediatrics, 2017)
The worldwide increase in asthma prevalence during the last decades and the re-emergence of vitamin D deficiency in many populations hinted towards an underlying association between these two conditions. Since asthma is presented with high incidence in childhood and neonatal vitamin D stores depend on maternal vitamin levels, a possible programming effect of maternal vitamin D status during gestation was suggested. Observational and longitudinal studies on this subject led to inconclusive results with glimmer of positivity. In the randomized controlled clinical trials (RCT) that followed, increased doses of vitamin D were tested in pregnant women being at high risk of having an asthmatic child. Although, the results of RCTs showed a potential association with rather asthma-related phenotypes than asthma per se, the low toxicity of Vitamin D supplements make it tempting to speculate that pregnant women at a high risk of obtaining a child with asthma may be benefited, especially if they are vitamin D deficient.